Does computed tomography scan add any diagnostic value to the evaluation of stab wounds of the anterior abdominal wall? A systematic review and meta-analysis. Issue 4 (April 2020) - Gachabayov, Mahir; Gogna, Shekhar; Samson, David; Latifi, Rifat
Abstract : BACKGROUND: The aim of this systematic review and meta-analysis was to evaluate whether computed tomography (CT) scan adds any diagnostic value in the evaluation of stab wounds of the anterior abdominal wall as compared with serial clinical examination (SCE). METHODS: PubMed, EMBASE, Cochrane Library, and MEDLINE via Ovid were systematically searched for records published from 1980 to 2018 by two independent researchers (M.G., R.L.). Quality assessment, data extraction, and analysis were performed according to the Cochrane Handbook for Systematic Reviews of Interventions. Mantel-Haenszel method with odds ratio (OR) and 95% confidence interval (95% CI) as the measure of effect size was used for meta-analysis. RESULTS: Three studies (1 randomized controlled trial and 2 observational studies) totaling 319 patients were included in the meta-analysis. Overall laparotomy rate was 12.8% (22 of 172 patients) in SCE versus 19% (28 of 147 patients) in CT. This difference was not significant (OR [95% CI], 0.63 [0.34–1.16]; p = 0.14). Negative laparotomy rate was 3.5% (6 of 172 patients) in SCE versus 5.4% (8 of 147 patients) in CT. The difference was not significant (OR [95% CI], 0.61 [0.20–1.83]; p = 0.37). CONCLUSION: This meta-analysis compared SCE with CT scan in patients presenting with stab wounds of the anterior abdominal wall and provided level II evidence showing no additional benefit in CT scan. Further observational and experimental clinical studies are needed to confirm the findings of this meta-analysis. LEVEL OF EVIDENCE: Systematic review and meta-analysis, level II.